Amelioration De La Maturite Des Entreprises En Gestion Des Risques Par La Maintenance - Hakim Nissoul; Fouad Riane; Ahmed Mousrij (European Scientific Journal, ESJ, 2017)
Statistics on accidents at work, particularly in Morocco, remain worryingly high. This situation raised a general awareness in the country and many decisions have been taken and corrective actions have been elaborated in order to enhance enterprise risk management maturity. This maturity is based on several key factors including maintenance.In this paper we propose a methodology to mitigate and control maintenance generated risks which in turn will allow enterprises to enhance their maturity in risk management.